H.J. Heinz M&A - Stowell, David (SAGE knowledge. Cases., 2016)
During December 2012, Jorge Paulo Lemann, a co-founder and partner at 3G, proposed to Warren Buffett that 3G and Berkshire Hathaway acquire H. J. Heinz Company. Lemann and Buffett, who had known each other for years, jointly decided that the Heinz turnaround had been successful and that there was significant potential for continued global growth. 3G informed Heinz CEO William Johnson that it and Berkshire Hathaway were interested in jointly acquiring his company. Johnson then presented the investors' offer of $70.00 per share of outstanding common stock to the Heinz board. This case study discusses this topic.